Dilema Etis Konsultan Pajak dalam Tax Planning: Studi Fenomenologi - Dewi, Anak Agung Istri Pradnyarani; Sudarma, Made; Baridwan, Zaki (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
Tax consultant helps the taxpayers taxation. Taxpayer requesting tax consultant do tax planning towards illegal. Tax consultant must adhere to the rules. This poses dilemma. This study was conducted to determine and observe how the tax consulting experience in facing dilemma when making tax planning using the approach of transcendental phenomenology. The results of this study have some form of dilemma is a dilemma due to unclear regulations and sympathy to the client. Through the experience of a tax consultant, this dilemma can be overcome with some consideration is to deepen awareness of rules and build awareness of the taxpayer.